Political programmes of British communism, 1944-1990. - Communist Party of Great Britain; Communist Party of Great Britain. Archive Trust (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2021)
The Communist Party of Great Britain (CPGB) created several commissions that aimed to construct political programmes in response to social, political, and economic developments in Britain and the Soviet Union. This collection hosts the papers of several commissions that sought to redraft the Party's flagship political manifesto: The British Road to Socialism. This was first published in 1951 with the personal approval of Joseph Stalin. It became a key battleground between various factions of the CPGB that sought to control the direction and agenda of the Party.
Date range: 1944-1990.
Keywords: Communist Party of Great Britain; Communism -- Great Britain